Effect of Teenage Pregnancy on Girl’s Education in Bukiende Sub-county, Mbale District - Sandra Kakayi (Uganda Christian University, 2024)
Many girls fail to enroll, attend school and complete the schooling cycle. This study examined the effect of teenage pregnancy on girl’s education in Bukiende Sub County in Mbale district. The purpose of the study was to examine the effect of teenage pregnancy on girl’s education in Bukiende Sub County, Mbale District. Specifically, the study was aimed at investigating factors contributing to teenage pregnancies among girls in Bukiende Sub County Mbale District and assesses their effects on the girls. It also examined interventions that can be taken to prevent teenage pregnancies and promote girls’ Education in Bukiende Sub County Mbale District. The study used qualitative research approach and a case study design of 15 participants who included teachers, parents, local leaders and teenage girls were interviewed. Documentary analysis was also used to gather relevant data to help answer research questions. Also female genital mutilation (FGM) has often caused limitations for school attendance since after FGM it means the girls is ready for marriage and early engagement in sexual activities and exposure to pornographic materials has the potential to contribute to teenage pregnancy. Findings also show that teenage pregnancy significantly increases the risk of suicidal ideation and attempted suicide for young people and this leads to school dropout and teenage pregnancies lead to emotional and psychological torture which disrupt schooling and a strong relationship between teenage pregnancy and a range of mental health problems. A number of interventions are needed to help prevent teenage pregnancies and promote the education of the girl child and providing life skills and raising awareness of the issue of girls’ education. There should be widespread existence of laws prohibiting negative cultural practices which lead to teenage pregnancies and address teenage pregnancies as a violation of universal human rights and also put in place approaches that to change norms at community level and reduce girls’ school dropout. The researcher recommendations that government and stakeholders should put in place measures of preventing abduction also called kidnapping which is considered as one of the factors contributing to teenage pregnancy and also sensitize parents and girls on the dangers of teenage pregnancies in a bid to prevent the vice. Other recommendations by the study include parents and schools should endeavor to mobilize enough funds to help provide the needs of the girl child. This will go a long way in mitigating problems related to teenage pregnancies and government together with stakeholders should there is need to put in place approaches that to change norms at community level and reduce girls’ school dropout.
Undergraduate Research